Many medals, but few interventions: the paradox of sports psychology research and Olympic combat sports - Andrade, A.; Dominski, F.; Andreato, L. (Sport Sciences for Health, 2021)
Background: In the Tokyo 2021 Olympics, combat sports (boxing, fencing, judo, karate, taekwondo, and wrestling) will play a leading role, constituting approximately 22% of all the contested medals. For competitive success, there is a strong connection between combat sports and high specific emotional burdens of matches.